Can a Short Intensive Course Affect Entrepreneurial Ability, Knowledge and Intent, or Further Entrepreneurial Study?: An Assessment of the SEED Programme, Dunedin, New Zealand. (October 2015) - Cornwall, Jon; Kirkwood, Jodyanne; Clark, Gavin J.; Silvey, Stephen; Appleby, Ruth D.; Wolkenhauer, Svea Mara; Panjabi, Jayashree; Gluyas, Eva; Brain, Chelsea; Abbott, Matthew
The SEED (Student Enterprise Experience in Dunedin) programme was developed as a four-week, intensive entrepreneurial 'boot camp' to provide a small group of participants with a highly experiential business course. Using pre-course and post-course surveys, the authors measured the entrepreneurial ability, knowledge and intentions of the sixteen SEED participants to determine whether the programme was successful as an educational format. The results showed that perceived entrepreneurial ability and knowledge significantly improved, while intent increased but not significantly. Almost all participants intended to start a business both before and after the course, while twice as many (six) indicated that they would undertake further formal study in entrepreneurship after the course compared to before. The data suggest that SEED is filling a niche in entrepreneurial development and support for budding entrepreneurs, with the course also facilitating local business development.